The Effect of Snakes and Ladders Games Stimulation on the Cognitive and Fine Motor Development of Preschool Children - Misniarti, Misniarti; Yossy Utario; Sri Haryani; Eko Suryani; Harmilah (JOSING: Journal of Nursing and Health, 2025)
This study aims to determine the effect of snake and ladder game stimulation on cognitive and fine motor development in preschool children in Rejang Lebong Regency. This research method uses a Quasi-experimental design with a two-group pre-posttest design. The results showed that the difference in fine motor development of respondents after the intervention was 1.47 in the intervention group and there was no difference in the control group. The results of the bivariate analysis found a p value of 0.000. In conclusion, there is a difference in the average fine motor and cognitive development in the intervention and control groups.   Keywords: Cognitive Development, Fine Motor Development, Snake and Ladder Game, Preschool